A Bibliometric Analysis of The Term DataOps - Nugroho, Antonius Sony Eko; Wella, Wella (Universitas Multimedia Nusantara, 2024)
This paper aims to analyze research trends of the term DataOps scientifically through bibliometric studies. Initial data were collected from Scopus database from 2018 to 2023 which resulted 34 documents, while in other hands we found more than 1000 documents in the Google Scholar database collected using Publish or Perish. Five years of data is collected because the scientific publications on term DataOps started to increase since 2018. We have deployed ``bibliometrix 3.0'', the r-package, and VOSviewer to analyze key literature aspects. Since the rise of the term DataOps, significant contribution to its definition and practical applications can be observed. DataOps enthusiasts collaborate to create a common principle for uniformly applying the methodology in the various data operation environments. DataOps will continue to evolve into an effective and reliable data management system. The findings in this study will help related researchers recognize the research trends of topics in DataOps research globally and suggest future research directions.